Beneficial insights into postbiotics against colorectal cancer - Song, Dingka; Wang, Xiuli; Ma, Yongjing; Liu, Ning-Ning; Wang, Hui (Frontiers in Nutrition, 2023)
Colorectal cancer (CRC) is one of the most prevalent and life-threatening cancer types with limited therapeutic options worldwide. Gut microbiota has been recognized as the pivotal determinant in maintaining gastrointestinal (GI) tract homeostasis, while dysbiosis of gut microbiota contributes to CRC development. Recently, the beneficial role of postbiotics, a new concept in describing microorganism derived substances, in CRC has been uncovered by various studies. However, a comprehensive characterization of the molecular identity, mechanism of action, or routes of administration of postbiotics, particularly their role in CRC, is still lacking. In this review, we outline the current state of research toward the beneficial effects of gut microbiota derived postbiotics against CRC, which will represent the key elements of future precision-medicine approaches in the development of novel therapeutic strategies targeting gut microbiota to improve treatment outcomes in CRC.